Pengaruh Profitabilitas Dan Leverage Terhadap Nilai Perusahaan Pada Perusahaan Sektor Industri Dasar Dan Kimia Di Bei Periode 2014-2018 - Iskandar, Nawal; Mandra, I Gede; Oktariyani, Gusti Ayu Sri (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2020)
This study is aimed to determine the effect of Profitability and Leverage on Firm Value. Profitability is measured by Return on Assets (ROA) and Leverage is measured by Debt to Equity Ratio (DER), while Firm Value is measured by Price to Book Value (PBV). The population of this research is Basic Industry and Chemicals Companies Sectors that listed on the Indonesia Stock Exchange. There are 17 companies as sample in this study which were obtained by purposive sampling method. Data collected by combaining cross-section and time-series data. Furthermore, panel data analyze by multiple linear regression analysis by using EViews software. The findings show that ROA has a positive and significant effect on firm value, while DER has no significant effect on firm value